Marine-origin Polysaccharides for tissue engineering and regenrative medicine. Chitosan and Fucoidan as illustrative examples - Reys, Lara Priscila Lopes (2020)
Marine polysaccharides are receiving wide attention not only from scientists but also from engineering and medical staff, given the several properties being reported for this class of biopolymers and based on the reputation gain by the terrestrial representatives. The marine environment is a source yet to be untapped, with several approaches being disclosed to promote the sustainable exploitation of marine biological resources. Conjugating the interesting properties with the sustainability of their use, the potential on the application of marine polysaccharides is, indeed, huge. In this chapter, the main properties and biological activities of marine polysaccharides will be explored, particularly the ones more relevant for application in a biomedical context, with a particular focus in two illustrative examples: chitosan and fucoidan. Both resemble chemical characteristics of glycosaminoglycans found in the human extracellular matrix, from which arises a particular interest regarding tissue engineering and regeneration.